Global Economic Prospects and the Developing Countries 1993 - World Bank (Washington, DC: World Bank, 2019)
This year's report focuses on the role of external finance in development, as external finance has an important bearing on the growth and economic prospects of developing countries. Chapters 1 and 2 describes the new pattern of external finance in the 1990s and the consequences of increased financial integration of developing countries with global capital markets. Chapters 3-5 addresses major issues in external finance, including the benefits of foreign direct investment, the sustainability and volatility of portfolio flows, and the imbalance between slow growth in aid flows and fast growth in the number of claimants eligible for aid. Finally, Chapters 6 and 7 discuss the outlook for the global economy over the next decade, examines developments in the international economic environment, and discusses the implications for developing country growth, both in aggregate and by region.